2022
DOI: 10.47368/ejhc.2022.203
|View full text |Cite
|
Sign up to set email alerts
|

Stop and Think! Exploring the Role of News Truth Discernment, Information Literacy, and Impulsivity in the Effect of Critical Thinking Recommendations on Trust in Fake Covid-19 News

Abstract: Covid-19-related fake news widely circulates on social media. This is problematic as people commonly do not process information on social media in a very critical manner. Also, when people encounter particular online content several times this tends to increase the content’s trustworthiness, sometimes irrespective of the accuracy of the provided information. Our study aims to explore whether, how, and for whom a simple critical thinking recommendation added to a social media newsfeed can aid people to better d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
3
19
0
1
Order By: Relevance
“…It also could be that discernment cannot directly predict vaccination behavior. It was found that discernment affects the trust of belief in the news [ 55 ], and trust could be related to vaccination behavior, as our data support. Thus, the mediation or moderation effects should be considered aside from testing the direct effects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It also could be that discernment cannot directly predict vaccination behavior. It was found that discernment affects the trust of belief in the news [ 55 ], and trust could be related to vaccination behavior, as our data support. Thus, the mediation or moderation effects should be considered aside from testing the direct effects.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, some potential participants could not reach this study during the pandemic. From previous studies, we know that discernment is related to previous knowledge [ 38 ], cognitive functioning [ 38 ], digital literacy [ 55 ], and personality traits [ 58 ]. In this study, we did not control for any of these factors, which could affect the discernment, beliefs or attitudes, and even vaccination behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Leuker et al (2022) revealed that only about half of respondents used strategies to discern between true and false information. Kruijt et al (2022) revealed that the use of such strategies can indeed make a difference. Similar to research on accuracy nudges (Pennycook et al, 2020), Kruijt et al (2022) explored whether a simple critical thinking recommendation added to a social media newsfeed could aid people in better discerning true news from false and reducing their trust in misinformation.…”
Section: Europeanmentioning
confidence: 99%
“…Kruijt et al (2022) revealed that the use of such strategies can indeed make a difference. Similar to research on accuracy nudges (Pennycook et al, 2020), Kruijt et al (2022) explored whether a simple critical thinking recommendation added to a social media newsfeed could aid people in better discerning true news from false and reducing their trust in misinformation. Their online experiment among Dutch-speaking participants showed that those who were exposed to the critical thinking recommendations showed less trust in misinforming messages compared to a control condition.…”
Section: Europeanmentioning
confidence: 99%
See 1 more Smart Citation